Symbolic interaction and inequality - Chen, Shing-Ling S. (Emerald Publishing Limited, 2024)
Acting as a follow up to Volume 41 of Studies in Symbolic Interaction (2013), Symbolic Interaction and Inequality explores further the concept of Radical Interactionism, a perspective of researching domination and subordination introduced by scholar Lonnie Athens. Demonstrating advancements made in Radical Interactionism over the past decade, chapters examine the omnipresent and insidious nature of inequality as well as its social construction among family members, cisgender and gender-diverse people, as well as university students and personnel, particularly college athletes. Highlighting fruitful accomplishments achieved by a range of symbolic interactionists, this volume exhibits the significance of studying inequality, a venture that not only enriches symbolic interactionism but human life as a whole.
Keywords: Social interaction.; Symbolic interactionism.; Equality.; Social Science -- Sociology -- General.; Sociology.; elektronické knihy; electronic books